New Spatial Possibilities of Railway Station: Everyday Heritage, Enjoyable Landscape. (2015) - Ye-Kyeong, Shin; Hye-Jin, Jung
Abstract: Railway became a major transportation means for distribution and people approximately a century and a half after it was first constructed in 1825 from England. In addition, the construction of railway station back then has physically occupied the city partially in a linear fashion and variously influenced the urban space.The importance of the railway station in the city was mentioned in the Building News in 1872, that the "Railway termini and hotels are to the nineteenth century what monasteries and cathedrals were to the thirteenth century." After 130 years, Ferrarini(2005) explained that while factories are isolated in the suburb area, railway station is one of the most industrial structures located in the center of the city supporting the city function as a complex facility. Furthermore, he referred to the railway station the possibility as a city facility among the typical facilities being decided by the function as a school, museum, library, City Hall or factory.From recent projects, such as Japan's Tokyo Station Restoration project, Paris' Gare du Nord and the surrounding area regenerating project, New York's High Line project, and Busan's Integrated Regeneration of the old harbor project, railway station, since the nineteenth century's industrial revolution, is not only functioning as the daily use, but also the accelerator in regenerating the old city with its historical background.Thus, this study applies recent cases occurred in geographically various locations such as Tokyo Station, Paris Gare du Nord, the High line Project, and Busan Station. Through the railway stations appearing in each instances, the urban application plan will be analyzed in a social-scientific way and discuss how railway station is not simply a temporary traffic facility for transporting, but a recyclable industrial heritage and a possibility as a urban space with enjoyment of the city scenery.